Sliding mode control for N‐coupled reaction‐diffusion PDEs with boundary input disturbances - Gu, Jian‐Jun; Wang, Jun‐Min (International journal of robust and nonlinear control, 2019)
Summary This paper develops the sliding mode control (SMC) design for N‐coupled reaction‐diffusion parabolic PDEs with boundary input disturbances. In order to reject the disturbances, the backstepping‐based boundary SMC law is constructed to steer the system trajectory to a suitable sliding surface and then maintain sliding motion on the surface thereafter, resulting in the exponential convergence to the zero equilibrium state. The well‐posedness of the closed‐loop system is established based on a detailed spectral analysis and Riesz basis generation. Finally, a simulation example is provided to illustrate the effectiveness of the SMC design.